Internship experience at foundever (2023)
This report is the result of my work experience during my internship at Foundever. During this time, I had the opportunity to actively participate in the work environment and apply certain knowledge acquired in my academic formation. Throughout the following sections, key aspects of my experience will be addressed, including a description of the company or organization, the context of the internship, my roles and responsibilities, the competencies acquired, as well as the contributions I made to the team and challenges I encountered during this internship, as well as their relevance to my professional and personal development.